Semi-professionals: emergency response as an additional task in current occupations. Issue 2 (5th August 2019) - Yousefi Mojir, Kayvan; Pilemalm, Sofie; Andersson Granberg, Tobias
Abstract : Purpose: The purpose of this paper is twofold: first, to identify occupational groups who can act as semi-professional first responders, in order to shorten the response times to frequent emergencies, and second, to identify related opportunities, challenges and needs of training, emergency supplies and information technology (IT) support. Design/methodology/approach: A case study approach was taken, combining future workshops, focus groups and an exercise. Network governance was used as an analytical lens. Findings: The identified potential groups are security guards, home care personnel, fire services day personnel and facility service personnel. The results show that semi-professionals have a large potential to complement professional resources by carrying out first response or supportive actions vital to the emergency, partly by using already existing cars and equipment. The identified needs include additional basic equipment such as fire extinguishers and first-aid kits, training in basic firefighting, first aid and risk assessment, as well as mobile phone application-based IT support to manage alarms. The major challenges are organisational, economic and juridical, including ambiguities in responsibilities and related insurances. The analysis recognises the new collaboration as a hybrid form of hierarchical government and network governance. Social implications: The study suggests that using semi-professional resources can be one of many innovative solutions to recent public sector challenges that have put a huge strain on professional emergency response organisations. Originality/value: The study provides a novel view of using semi-professional resources in emergency response, based on the joint perspectives of various occupational groups, and the fire services.